Growth hormone therapy and chromosomal mosaicism in turner syndrome: 25 years of growth outcomes in Taiwan - Chang, Yu-Ting; Huang, Ying-Hua; Lo, Fu-Sung (Frontiers in Endocrinology, 2025)
BackgroundTurner syndrome (TS), a chromosomal disorder affecting females, is commonly associated with short stature due to haploinsufficiency of the SHOX gene. Recombinant human growth hormone (rhGH) and estrogen replacement therapy (ERT) are standard treatments to improve height and induce puberty. However, the impact of chromosomal mosaicism and other clinical variables on long-term growth outcomes remains controversial, particularly in Asian populations.ObjectiveTo evaluate the influence of karyotype and other clinical predictors on growth velocity and final adult height in Taiwanese patients with TS undergoing rhGH and ERT.MethodsThis 25-year retrospective multicenter study included 107 TS patients treated at three medical centers between 1997 and 2022. Patients were stratified into non-mosaic and mosaic karyotype groups. Growth patterns, treatment duration, and final adult height were assessed. Multivariable linear regression was used to identify predictors of growth outcome, including karyotype, bone age, baseline height, parental heights, IGF-1 levels, and pubertal status.ResultsrhGH therapy began at a mean age of 11.0 ± 2.78 years (non-mosaic: 11.55 ± 2.76; mosaic: 10.50 ± 2.74). Patients with mosaic TS exhibited higher mean growth velocities during rhGH therapy without significant differences (p >0.05). ERT was initiated at a mean age of 15.10 ± 1.76 years in both groups. Heights at ERT initiation were 142.26 cm (non-mosaic) and 144.26 cm (mosaic). However, final adult height did not significantly differ between non-mosaic groups (148.31 ± 5.09 cm) and mosaic (149.39 ± 5.5 cm), respectively (p > 0.05). Regression analysis identified baseline bone age (β = –2.35, p < 0.0001), initial height (β = 0.55, p < 0.0001), and mid-parental height (β = 0.39, p = 0.0056) as significant predictors of final height. Karyotype, IGF-1, and pubertal status were not independently associated with growth outcomes.ConclusionGrowth hormone treatment in TS is beneficial, but final adult height is complex. Karyotype, including mosaicism, isn’t a primary driver of adult height; instead, factors such as bone age at treatment initiation, pre-treatment height, and mid-parental height are stronger predictors. This emphasizes the need for early diagnosis, individualized treatment plans focusing on clinical assessments, and appropriately timed hormonal interventions.